الاساليب المستحدثة ضمن إستراتجية الكشف عن الجرائم المنظمة - محمدي محمد أيمن - بعيرة إسلام (جامعة المسيلة, 2025)
Organized crime is considered one of the most terrifying crimes due to its diverse patterns and forms, especially since it is practiced by the most dangerous criminals. The phenomenon of organized crime as a criminal method was one of the oldest forms of violence known to humanity throughout various eras of human history. At the end of the last century, it became one of the most dangerous to societies, including Algerian society. Organized crime is no longer practiced to attack specific individuals, as was the case in the past. Today, it aims to spread terror and fear among governments, especially given its significant impact on individuals and the state as a result of the most serious crimes practiced by criminal organizations. These crimes, such as human organ trafficking, instill terror and fear in individuals, and threaten the security of society and the state, such as money laundering and drug trafficking, along with other crimes stipulated in the Algerian Penal Code. Organized crime currently represents one of the most important challenges facing the Algerian state and most countries around the world. This is due to the fact that organized crime is characterized by its international nature, threatening the stability and security of more than one country and a single organization, negatively impacting the social and economic stability of these countries. The necessity of uncovering the crimes of organized gangs, combating them, arresting them, prosecuting them and applying the necessary penalties against them required a set of search and investigation procedures by the judicial police, as it is the competent authority to uncover this type of crime. The aim of these procedures is to uncover them and know all the circumstances in which they were committed, as well as to investigate all information related to their occurrence. The Algerian legislator has created new and more effective means to uncover them in order to complete the process successfully following the amendment of the Algerian Code of Procedure by Law No. 06-22 of 78 December 20, 2006 amending the Code of Criminal Procedure, which are: leakage – interception of correspondence – recording voices – taking pictures.